A study of the job description of library personnel of the College of Arts and Letters Library and the College of Social Sciences and Philosophy Library of the University of the Philippines Diliman - Cruz, Luis Ezra D. (2009)
The study aims to examine the job descriptions of personnel of library units in University of the Philippines Diliman. It intends to present the duties listed in the respective job description of the library staff members and see if it matches with the duties they perform. The two library units included in the study are the College of Arts and Letters Library and the College of Social Sciences and Philosophy Library in UP Diliman.